Generation of sustaintable development syntethic indicator, Peru 2015 - Ilasaca Cahuata, Edwar (2018)
It is proposed in this research  Synthetic Indicators generation on Sustainable Development Peru - 2015, through  Factorial Analysis application  - Main components method  in order to reduce the dimensionality from a set of sustainable development indicators to a set of compound Independent factors. The research design was strategic quantitative, non - experimental, cross – sectional,  correlational, and the  data collection technique was from secondary and documentary sources, using  INEI - Peru National Decision - Making System  and the National System database Of Peruvian Environmental Information - in order to obtain the eight indicators considered in this study. Data processing and analysis were performed using SPSS v. 23 and EXCEL which allowed obtaining the correlation matrix, main components,  rotated main components, and the weight index for each of the indicators and  determination of the indicators of sustainable development of each region. Two main factors or components were obtained to explain 74.343% of the data variability, the first factor grouped four indicators to which we denominate socioeconomic factor and explains the 38.278%. The second grouped the remaining four which we denominate Socio-environmental and explains the 36.065%. Finally, we generate the Synthetic Indicators of Sustainable Development for each of the regions for validation and we compare them with the Regional Competitiveness Index.